UNDERSTANDING VISITOR PREFERENCES IN OLD OYO NATIONAL PARK, NIGERIA - Arowosafe, F. C.; Kuuder, C. J. W.; Bokyaa, D. T. (UDS International Journal of Development, 2021)
This study sheds light on visitors’ preferences in Old Oyo National Park (Nigeria) and how these preferences contributed to their travel experience. A total of 120 visitors were reached via convenience sampling employing questionnaire administration. Their preferences were measured with the aid of a Likert scale and choice cards. Data collected were analyzed using descriptive statistics and conditional logit specification for inferential statistics. The results revealed that entrance fees, availability of affordable chalet accommodation, wildlife viewing opportunities and visits to the relics of the old city wall of Oyo Ile were the significant site predictors of choosing the park as a preferred tourist destination. Easy access within the park and good staff courtesies also had high means of 4.21 and 4.16 respectively, demonstrating site features and hospitality services rendered lends credence to visitor decision on destination choice. The park management needs to continually research on attractions and make efforts at improving such to entice repeat visits. Keywords: Old Oyo National Park, Hospitality Services, Visitor Preferences, Site Features, Experiences